Integration of the Civil Society Development of the Prophet Muhammad: Historical Perspective - Muhammad Husni (Pappaseng: International Journal of Islamic Literacy and Society, 2022)
Because it is believed that intellectual intelligence alone is insufficient to make humans more civilized, many community-based educational institutions offer Islamic-based character education. This article introduces the Prophet Muhammad PBUH. as an exemplary figure that we should emulate through the following discussions: knowing the education obtained by Muhammad bin Abdullah prior to being appointed as Prophet and Apostle, and knowing the figure of the Prophet Muhammad. This study is based solely on qualitative library research (library research). Based on a search of numerous literatures pertaining to the formation of Islam during the Mecca period during the time of the Prophet Muhammad, First, the evolution of Islam as practiced by the Prophet Muhammad after he became a prophet and apostle. Second, understanding the evolution of the education development system implemented by the Prophet Muhammad for those who are educated beginning with their immediate family. Third, revealing the fruits of the Prophet Muhammad's education to members of the Arab community and Civil Society who are unfamiliar with Islam. This paper invites educators to revisit and implement the concept of Islamic education that has been exemplified and applied by the Prophet Muhammad in order to alleviate the concern that every teacher or educator in the millennial era has regarding the difficulty of maintaining student discipline in the midst of the rapid advancement of technology.